Pengembangan Pendidikan Islam dengan Strategi Teungku Chiek di Rundeng Aceh Indonesia - Anwar, Dede Saepul (Lembaga Yasin AlSys, 2023)
Aceh was under Dutch rule for decades. During this time, the public couldn’t access education due to restrictions put in place by the Dutch empire. Access to quality schools is limited to children from the upper class, as most children have difficulty getting an education. As a result, many kids struggle to get an education that includes Islamic education— even if they are from the upper class. Understanding Aceh’s only province with Islamic syari’ah is the main goal of this paper. After that, solutions provided by Teungku Chiek Dirundeng for building Islamic education are sought out. Through his efforts, he helped the Aceh community come together and find solutions to their problems. The story of Teungku Chiek Dirundeng is recorded in Aceh’s saga and written directly into Dutch history books. It’s one of the religious leaders in Aceh who contributed to building the civilization of human life by educating people. This research uses qualitative methods to examine the history and strategies of Teungku Chiek Dirundeng to develop an Islamic-based education system in Aceh. Researchers reviewed every public document published between 1960 and the present day for their research. These documents showed that Teungku Chiek Dirundeng believed building Islamic schools was the best way to promote Islamic education. Pesantren, pronounced Dayah in Indonesian, is an educational institution founded by Muslim scholars. It's based in Meukek, Labuhan Haji and Rundeng areas and is known for its ability to mobilize the community to work together. Only a few researchers have studied the history of Islamic leaders. One of these people is Aceh’s Sultan Hamengku Buwono II. He led the community to create dayah, which is the first step in forming an Islamic education system. Before that point, he helped people establish basics like religion and its rituals in Aceh.